Diagnosis of keratoconus in a young male by electrophysiological test findings: A case report. Issue 27 (8th July 2022) - Yan, Weiming; Chen, Yanjin; Chen, Xiaohong; Ye, Qian; Wang, Yutong; Jiang, Chuan; Zheng, Xiangrong; Wang, Yunpeng; Chen, Meizhu
Abstract : Rationale: The purpose of this report was to describe the diagnostic process of a case of keratoconus (KCN) after electrophysiological examination. Patient concerns: A 23-year-old male army officer presented with decreased visual acuity (VA) in the left eye for 5 months. Best-corrected VA was 20/20 in the right eye and 20/300 in the left eye. The cornea and lens were clear in both eyes with a normal anterior chamber. No specific abnormalities were found on fundus photography, optical coherence tomography, fundus fluorescein angiography (FFA), indocyanine green angiography (ICGA), or full-field electroretinography (ffERG) of both eyes. Pattern visual-evoked potentials (PVEP) detected a reduced amplitude and delayed peak time of the P100-wave in both eyes, which was more severe in the left eye. The amplitude and peak time of the P2-wave in flash VEP (FVEP) were comparable in both eyes and were within the normal ranges. Diagnosis: Corneal topography was performed, and KCN was diagnosed by the presence of an asymmetrical bowtie pattern in both eyes, which was worse in the left eye. Interventions: Transepithelial corneal collagen cross-linking was performed. Outcomes: The BCVA of both eyes remained stable after treatment at follow-up. Lessons: KCN should be suspected in cases of unimproved VA and significant irregular stigmatism, while no obvious lesions exist in other parts of the eyes. The evidence of lesion location by electrophysiological examinations could sometimes be of favor in diagnosing KCN.